Effects of animal grazing on vegetation biomass and soil moisture on a typical steppe in Inner Mongolia, China. Issue 1 (15th September 2021) - Lin, Xi; Zhao, Hongbin; Zhang, Shengwei; Li, Xiaoyuan; Gao, Wenlong; Ren, Zhaoyi; Luo, Meng
Abstract: Grasslands play a very important role in the water and carbon cycle of arid and semi‐arid areas, where they are the main type of steppe globally. With this said, research into grassland ecological processes mostly consists of single‐factor controlled experiments such as precipitation, temperature or grazing, and few studies have investigated the effects of synergistic interactions between multiple factors on grassland hydrological, soil and vegetation processes. In this study, we set up a prohibited grazing area in a typical area of the Xilingole Steppe in Inner Mongolia, China. Vegetation (species richness (SR), above‐ground biomass (AGB), below‐ground biomass (BGB), etc.), precipitation and the soil moisture of 5 cm, 10 cm, 15 cm and 30 cm depths were observed continuously from 2015 to 2018. The results indicate that the species number in areas where grazing is prohibited is higher than where it is grazed, and the number and species of dominant species changes with grazing prohibition time. The AGB and BGB of prohibited areas is higher than grazed areas, and the variance rate of AGB increased rapidly (20% and 45%) at the first 2 years and then stabilized (52% and 55%), but BGB's variance rate increased slowly from 12% to 20%. The soil moisture content in the study area is higher in the surface layer than in the deeper layers. In the grazing prohibition zone, the above ground biomass (AGB) and belowground biomass (BGB) were both significantly correlated with volumetric water content (VWC) at the 0.01 level. In grazing areas, there was no significant correlation between AGB and soil moisture, and the coefficient of determination between BGB and VWC was 0.6127 ( p  < 0.01). SR did not have a significant relationship with soil moisture but indirectly response to it through BGB, especially in prohibited site. These results are important for understanding water cycle processes, grazing management and address food security issues across steppe in arid and semi‐arid regions.